SOSYAL GÜVENLİK HARCAMALARI VE İKTİSADİ BÜYÜME ARASINDAKİ İLİŞKİNİN ANALİZİ: TÜRKİYE ÖRNEĞİ - Yılmaz, Tuğba (Turkish Management Review, 2023)
The different levels of development and socio-economic structures of countries play a determining role in the share they allocate from their national income to social security expenditures. After the II. World War, with the adoption of the social state approach, countries increased the share allocated from their national income to social security expenditures. This increase stemmed from there is a direct relationship between social security and the level of economic development of the country. Nowadays, many studies aim to analyze this relationship, but there is a scarcity of studies specifically conducted in Turkiye that draws attention. Therefore, this study aims to analyse the long-run relationship between social security expenditures and economic growth in Türkiye for the period 1980-2021. For this purpose, Engle-Granger cointegration and Granger causality tests were performed on the relevant variables.The results show that there is a long-run relationship between social security expenditures and economic growth, and this relationship is unidirectional from social security expenditures to economic growth. Long-term coefficient estimates revealed that a 1% change in social security expenditures will lead to a 1.4% change in GDP per capita.

Ülkelerin gelişmişlik düzeylerinin ve sosyo-ekonomik yapılarının farklı olması milli gelirlerinden sosyal güvenlik harcamalarına ayırdıkları payda belirleyici bir rol oynamaktadır. Özellikle İkinci Dünya Savaşı'nı izleyen yıllarda sosyal devlet görüşünün benimsenmesiyle birlikte ülkelerin milli gelirden sosyal güvenlik harcamalarına ayırdıkları payın arttığı gözlemlenmektedir. Bu artış sosyal güvenlik ile ülkenin iktisadi gelişme düzeyi arasında doğrudan bir ilişki olduğu düşüncesinden kaynaklanmıştır. Günümüzde bu ilişkiyi analiz etmeyi amaçlayan birçok çalışma olmakla birlikte, Türkiye özelinde yapılan çalışmaların azlığı dikkat çekmektedir. Bu nedenle bu çalışma Türkiye'de 1980-2021 dönemi boyunca sosyal güvenlik harcamaları ile iktisadi büyüme arasında uzun dönemli bir ilişkinin olup olmadığını analiz etmeyi amaçlamaktadır. Çalışmanın amacı doğrultusunda ilgili değişkenlere Engle-Granger eşbütünleşme ve Granger nedensellik testleri yapılmıştır. Çalışmadan elde edilen bulgulara göre sosyal güvenlik harcamalarından iktisadi büyümeye doğru tek yönlü bir ilişki olduğu tespit edilmiştir. Buna göre sosyal güvenlik harcamalarında meydana gelecek olan %1'lik bir değişim kişi başına düşen GSYH'de %1,4'lük bir değişime yol açacaktır.
Keywords: Eşbütünleşme; Cointegration; Zaman Serisi Analizi; Economic Growth; Sosyal Güvenlik; Time Series Analysis; İktisadi Büyüme; Social Security; 8. Economic growth; 1. No poverty